The time course of hypoxia effects using an aviation survival trainer - Borden, Cammi K.; McHail, Daniel G.; Blacker, Kara J. (Frontiers in Cognition, 2024)
Reduced environmental oxygen levels at high altitudes can result in hypoxic hypoxia, which remains a primary threat in tactical aviation. Hypoxia broadly impairs cognition and can degrade a pilot's ability to safely operate the aircraft. Current hypoxia countermeasures include aircraft life support systems that deliver supplemental oxygen and using controlled hypoxia exposures to train aviators to recognize symptoms. To maximize the effectiveness of these countermeasures, it is critical to understand how hypoxia impacts performance and associated neurocognitive outcomes. We previously showed that a neural marker that indexes sensory processing integrity is sensitive to hypoxia impairment. Here, we extend this line of research closer to the training environment by using hypoxia simulation equipment currently standard in aviation survival training. In a single-blind, repeated-measures, counterbalanced design, we exposed 34 healthy participants to either normoxic air (ground level) or normobaric hypoxia (altitude equivalent gradually increasing from 10-25k') for 20 min after a 10 min baseline at ground level. During the exposure, participants completed a cognitive assessment battery while passively elicited neural responses to auditory tones were recorded using electroencephalography (EEG). Participants reported their hypoxia symptoms throughout and upon completion of their exposures. We found that the hypoxia exposure rapidly elicited the predicted physiological responses in peripheral oxygen saturation (decrease) and heart rate (increase) within 2-3 minutes of exposure onset. On average, participants reported hypoxia symptoms in a delayed manner, approximately 8 min following the exposure onset. Performance on the cognitive tasks was relatively unaffected by hypoxia for basic tasks including Stroop, fine motor tracking, color vision and arithmetic, but was significantly degraded by hypoxia for more advanced tasks that combined a visual search component with Stroop and a working memory task. EEG activity associated with pre-attentive auditory processing was impaired on average shortly after the first symptom report, approximately 10 min from exposure start. Together, these results move hypoxia research closer to conditions encountered in aviation survival training and support the use of training devices for future hypoxia research.